Tingkat Kepatuhan Mahasiswa Universitas Bangka Belitung Dalam Tertib Berlalu Lintas Di Wilayah Hukum Provinsi Kepulauan Bangka Belitung Tahun 2021-2023 - Jusmi, Delvia; Darc Noviayanti Manik, Jeanne; Toni (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
The compliance level of student in traffic dicipline refers to the extent to which students adhere to traffic rules and regulations while driving or walking on the road. This study aims to determine the traffic compliance level of Bangka Belitung University students according to Law No. 22 of 2009. The research employs an empirical juridical method with a sociological legal approach and qualitative descriptive analysis. The sampling method used is Purposive Sampling with the Maximum Variation Sampling technique. The results show that the compliance level of Bangka Belitung University of this study indicate that the level of compliance level Bangka Belitung University students falls within the Identification scale. Among 379 student surveyed. 184 admitted to violating traffic rules under urgent circumstances, and 120 cited negligence, placing 304 students within this scale. Twenty-six students were on the third or highest scale, Internalization, and 87 students were on the first scale, Compliance, indicating violations due to the absence of traffic police. Field observations also confirmed tat many Bangka Belitung Universitystudents do not comply with traffic regulations within the campus environment. Therefore, active participation from both the police and the university is needed to bridge this issue and create traffic discipline.